Technical Skills Development in Civil Services: A Conundrum from the Perspective of Pre-Service Teachers in South African University of Technologies - M. S. A. Maeko (Research Developments in Science and Technology Vol. 10, 2022)
The amalgamation of theory and practical hands-on skills in technical subjects is critical for creating employment opportunities for the youth. However, infusing the practical hands-on skills into theory in school technical subjects does not yield the required results. In the context of Civil Services specialization in Civil Technology, this study explores the misalignment between the Department of Basic Education (DBE) curriculum and technical hands-on skills development at selected South African schools, which leaves learners at risk of graduating from Grade 12 without the much needed technical skills and abilities, and how this can be remedied .This study is aimed to highlight the existing challenges hindering learners hands-on technical skills development and advise the Department of Basic Education how such could be mitigated. The study established pre-service teachers’ frustrations with the DBE for not supporting schools in terms of equipment and materials. Besides recommending that resources and infrastructure be supplied, more time should also be allocated for developing appropriate practical skills in schools. From the study, radical changes to the Senior Phase curriculum are proposed with a view of creating space for practical skills development.